Modelo de gestión y dirección en los proyectos de infraestructura desarrollados por RECOPE S.A. - Lara-Murillo, Nelson; Ramírez-Herrera, Walter (Instituto Tecnológico de Costa Rica, 2012)
RECOPE is a state company that handles the import, processing and distribution of hydrocarbons for the last 45 years. RECOPE provides about 70% of the energy that the country needs for its economic and social activities. The vision and mission of this company are focused on ensuring the efficient supply of hydrocarbons to the domestic market, taking into account the customer satisfaction. To fulfill the above, RECOPE requires an investment in infrastructure projects that generate items or services that meet customer needs. The problem that RECOPE is facing, is that projects do not comply with their objectives in time, cost, scope and quality. The reason for this is the absence of an adequate project management, as evidenced by the strategic plan 2010-2014 and the report of the Comptroller General of the Republic DFOE-AE-IF-11-2011. It is for that reason, we proceeded to make a diagnosis of the situation by applying the technique of problem tree analysis, expert judgment and interviews with the heads of the departments to determine possible causes and effects that lean projects to fall behind on time, impacting the cost, scope and quality. Because some of the solutions are of an economic nature, the answer was to adopt the development of a model that provides better management and administration of projects in RECOPE. This model has the primary objective to create order and facilitate the verification of each of the elements required for proper project management. The main recommendations that were raised for this model are: - Set the figure of the project manager as an integrator of the phases since the project start until finished. - Create the organizational structure of the company in order to manage the projects following the guidelines established in the PMBOK®. It is suggested to evaluate the change from a functional structure to a projectized structure.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica. Área Académica de Gerencia de Proyectos, 2012.
Keywords: Inversión estratégica; Promoción; Negociación; Financiamiento; Diseño